High plasma apolipoprotein B identifies obese subjects who best ameliorate white adipose tissue dysfunction and glucose-induced hyperinsulinemia after a hypocaloric diet. Issue 1 (18th June 2018) - Bissonnette, Simon; Saint -Pierre, Nathalie; Lamantia, Valerie; Leroux, Catherine; Provost, Viviane; Cyr, Yannick; Rabasa -Lhoret, Remi; Faraj, May
ABSTRACT: Background: To optimize the prevention of type 2 diabetes (T2D), high-risk obese subjects with the best metabolic recovery after a hypocaloric diet should be targeted. Apolipoprotein B lipoproteins (apoB lipoproteins) induce white adipose tissue (WAT) dysfunction, which in turn promotes postprandial hypertriglyceridemia, insulin resistance (IR), and hyperinsulinemia. Objective: The aim of this study was to explore whether high plasma apoB, or number of plasma apoB lipoproteins, identifies subjects who best ameliorate WAT dysfunction and related risk factors after a hypocaloric diet. Design: Fifty-nine men and postmenopausal women [mean ± SD age: 58 ± 6 y; body mass index (kg/m 2 ): 32.6 ± 4.6] completed a prospective study with a 6-mo hypocaloric diet (−500 kcal/d). Glucose-induced insulin secretion (GIIS) and insulin sensitivity (IS) were measured by 1-h intravenous glucose-tolerance test (IVGTT) followed by a 3-h hyperinsulinemic-euglycemic clamp, respectively. Ex vivo gynoid WAT function (i.e., hydrolysis and storage of 3 H-triolein–labeled triglyceride-rich lipoproteins) and 6-h postprandial plasma clearance of a 13 C-triolein–labeled high-fat meal were measured in a subsample ( n  = 25). Results: Postintervention first-phase GIISIVGTT and total C-peptide secretion decreased in both sexes, whereas second-phase and total GIISIVGTT and clamp IS were ameliorated in men ( P  < 0.05). Baseline plasma apoB was associated with a postintervention increase in WAT function ( r  = 0.61) and IS (glucose infusion rate divided by steady state insulin (M/Iclamp ) r  = 0.30) and a decrease in first-phase, second-phase, and total GIISIVGTT ( r  = −0.30 to −0.35) without sex differences. The association with postintervention amelioration in WAT function and GIISIVGTT was independent of plasma cholesterol (total, LDL, and HDL), sex, and changes in body composition. Subjects with high baseline plasma apoB (1.2 ± 0.2 g/L) showed a significant increase in WAT function (+105%; P  = 0.012) and a decrease in total GIISIVGTT (−34%; P  ≤ 0.001), whereas sex-matched subjects with low plasma apoB (0.7 ± 0.1 g/L) did not, despite equivalent changes in body composition and energy intake and expenditure. Conclusions: High plasma apoB identifies obese subjects who best ameliorate WAT dysfunction and glucose-induced hyperinsulinemia, independent of changes in adiposity after consumption of a hypocaloric diet. We propose that subjects with high plasma apoB represent an optimal target group for the primary prevention of T2D by hypocaloric diets. This trial was registered at BioMed Central as ISRCTN14476404.